Challenging the Frontiers of Poverty Reduction (CFPR) - targeting the ultrapoor- targeting social constraints: Annual work plan, January to December 2003 - BRAC (© BRAC, 2016)
1. Introduction 2. Five year perspective plan 3. Annual work plan 2003